Detecting Medication Risks among People in Need of Care: Performance of Six Instruments - Dreischulte, Tobias; Sanftenberg, Linda; Hennigs, Philipp; Zöllinger, Isabel; Schwaiger, Rita; Floto, Caroline; Sebastiao, Maria; Kühlein, Thomas; Hindenburg, Dagmar; Gagyor, Ildikó; Wildgruber, Domenika; Hausen, Anita; et al. (International Journal of Environmental Research and Public Health, 2023)
Introduction: Numerous tools exist to detect potentially inappropriate medication (PIM) and potential prescribing omissions (PPO) in older people, but it remains unclear which tools may be most relevant in which setting. Objectives: This cross sectional study compares six validated tools in terms of PIM and PPO detection. Methods: We examined the PIM/PPO prevalence for all tools combined and the sensitivity of each tool. The pairwise agreement between tools was determined using Cohen’s Kappa. Results: We included 226 patients in need of care (median (IQR age 84 (80–89)). The overall PIM prevalence was 91.6 (95% CI, 87.2–94.9)% and the overall PPO prevalence was 63.7 (57.1–69.9%)%. The detected PIM prevalence ranged from 76.5%, for FORTA-C/D, to 6.6% for anticholinergic drugs (German-ACB). The PPO prevalences for START (63.7%) and FORTA-A (62.8%) were similar. The pairwise agreement between tools was poor to moderate. The sensitivity of PIM detection was highest for FORTA-C/D (55.1%), and increased to 79.2% when distinct items from STOPP were added. Conclusion: Using a single screening tool may not have sufficient sensitivity to detect PIMs and PPOs. Further research is required to optimize the composition of PIM and PPO tools in different settings.
CRIS-Team Scopus Importer:2023-02-24
Keywords: adverse drug reaction; inappropriate medication; nursing home residents; polypharmacy; prescribing omission